Prejudice : its social psychology - Brown, Rupert (Oxford, UK : Blackwell, 1995)
This book is about: The Nature of Prejudice; Prejudiced Individuals; Social categorization and Prejudice...
Keywords: Psychology; Prejudice; Stereotype; Prejudices; Prejudices in children; Stereotype (Psychology); Social psychology